EULAR/EFORT recommendations for management of patients older than 50 years with a fragility fracture and prevention of subsequent fractures. Issue 5 (22nd December 2016) - Lems, W F; Dreinhöfer, K E; Bischoff-Ferrari, H; Blauth, M; Czerwinski, E; da Silva, JAP; Herrera, A; Hoffmeyer, P; Kvien, T; Maalouf, G; Marsh, D; Puget, J; et al.
Abstract : The European League Against Rheumatism (EULAR) and the European Federation of National Associations of Orthopaedics and Traumatology (EFORT) have recognised the importance of optimal acute care for the patients aged 50 years and over with a recent fragility fracture and the prevention of subsequent fractures in high-risk patients, which can be facilitated by close collaboration between orthopaedic surgeons and rheumatologists or other metabolic bone experts. Therefore, the aim was to establish for the first time collaborative recommendations for these patients. According to the EULAR standard operating procedures for the elaboration and implementation of evidence-based recommendations, 7 rheumatologists, a geriatrician and 10 orthopaedic surgeons met twice under the leadership of 2 convenors, a senior advisor, a clinical epidemiologist and 3 research fellows. After defining the content and procedures of the task force, 10 research questions were formulated, a comprehensive and systematic literature search was performed and the results were presented to the entire committee. 10 recommendations were formulated based on evidence from the literature and after discussion and consensus building in the group. The recommendations included appropriate medical and surgical perioperative care, which requires, especially in the elderly, a multidisciplinary approach including orthogeriatric care. A coordinator should setup a process for the systematic investigations for future fracture risk in all elderly patients with a recent fracture. High-risk patients should have appropriate non-pharmacological and pharmacological treatment to decrease the risk of subsequent fracture.